Vision problems among children with oculo-cutaneous albinism attending special education schools in the Northern Province of South Africa - Raliavhegwa, Mashudu (University of Limpopo, 2001)
Refer to document
Thesis (M. OPT.) -- University of Limpopo, 2001
Keywords: Oculo-cutaneous; Low vision; 618.92097; Ophthalmology -- Health aspect -- South Africa; Geriatric ophthalmology -- Albinism -- South Africa